Incidence of Intermediate-stage Age-related Macular Degeneration in Patients With Acquired Immunodeficiency Syndrome - Jabs, Douglas A.; Van Natta, Mark L.; Pak, Jeong Won; Danis, Ronald P.; Hunt, Peter W. (American journal of ophthalmology, 2017)
To evaluate the incidence of intermediate-stage age-related macular degeneration (AMD) in patients with acquired immunodeficiency syndrome (AIDS). Cohort study. Patients enrolled in the Longitudinal Study of the Ocular Complications of AIDS (LSOCA) underwent 5- and 10-year follow-up retinal photographs. Intermediate-stage AMD (AREDS stage 3) was determined from these photographs by graders at a centralized Reading Center, using the Age-Related Eye Disease Study-2 grading system. The incidence of AMD in LSOCA was compared with that in the Multi-Ethnic Study of Atherosclerosis (MESA), a Human Immunodeficiency Virus (HIV)-uninfected cohort, which used a similar photographic methodology. The incidence of AMD in LSOCA was 0.65/100 person-years (PY). In a multivariate analysis the only significant risk factor for AMD in LSOCA was smoking; the relative risk vs never-smokers was 3.4 for former smokers (95% confidence interval [CI] 1.3, 9.5; P = .02) and 3.3 for current smokers (95% CI 1.1, 9.7; P = .03). Compared with the MESA cohort, the race/ethnicity- and sex-adjusted risk of AMD in LSOCA was 1.75 (95% CI 1.16, 2.64; P = .008), despite the fact that the mean age of the MESA cohort was 17 years greater than the LSOCA cohort (61 ± 9 years vs 44 ± 8 years). Patients with AIDS have a 1.75-fold increased race- and sex-adjusted incidence of intermediate-stage AMD compared with that found in an HIV-uninfected cohort. This increased incidence is consistent with the increased incidence of other age-related diseases in antiretroviral-treated, immune-restored, HIV-infected persons when compared with HIV-uninfected persons.